Cost-related dental non-attendance in older adulthood: evidence from eleven European countries and Israel - Listl, Stefan (Gerodontology, 2016)
Background Although relevant for health policy, so far only little is known about the extent to which persons avoid dental attendance because of associated costs. Objectives To examine the cost-relatedness of dental non-attendance in various older adulthood populations. Material and methods Secondary analyses were conducted of data from wave 1 of the Survey of Health, Ageing, and Retirement in Europe (SHARE), which includes unique information on recent dental non-attendance and care foregone due to costs by persons aged 50+ from eleven European countries and Israel. Multivariate logistic regression analysis was used to detect differences in the extent to which dental non-attendance is attributable to associated costs. Results The study sample comprised 13 935 persons who did not access dental care within the past year. Levels of cost-related non-attendance differed between the twelve examined countries, ranging from 6.8% in Israel to 0.5% in Austria. Cost-related non-attendance was 47% less likely among persons with good as compared to compromised chewing ability (Odds Ratio: 0.53; 95% CI: 0.43-0.66). Cost-related non-attendance was 33% less likely among persons with tertiary as compared to (pre-) primary educational attainment (Odds Ratio: 0.67; 95% CI: 0.47-0.96). Cost-related dental non-attendance was significantly more likely among persons with low levels of general health (Odds Ratio for lowest vs. highest level of general health: 3.05; 95% CI: 1.88-4.95). Conclusions The findings of the present study suggest that a relatively small proportion of dental non-attendance in older adulthood is cost-related. For specific population subgroups in various countries, however, dental care costs may still pose a relevant barrier to dental care.